Observations on the Avifauna of Mount Harriett National Park, South Andaman (A & N Islands) - Chandra, Kailash; Rajan, P. T. (Indian Forester, 1996)
The present paper reports the occurrence of 88 species ot birds from different localities or Mount Harriett National Park, South Andamans.